ANALISIS MANAJEMEN LABA, INTENSITAS MODAL, DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN: STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR SEKTOR INDUSTRI BARANG KONSUMSI SUB SEKTOR INDUSTRI MAKANAN & MINUMAN DI BEI - Santaria, Nola; Wibowo, Agus Satrya; Setiawan, Ricky Yunisar (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2025)
This study examines the relationship between earnings management practices, capital intensity, and dividend policy with firm value. The study was conducted on manufacturing companies in the food and beverage industry sector listed on the Indonesia Stock Exchange for the 2019-2021 period. Using a purposive sampling method, this study involved 18 companies and produced 54 observation data. Statistical analysis was carried out using multiple regression through SPSS version 26 software. The results of the study indicate that capital intensity and dividend policy do not have a significant effect on firm value, while earnings management has a positive impact on firm value